Bacteriocin production and sensitivity - Kecerová, K; Pristas, P; Javorský, P (Folia microbiologica, 2004)
Using an overlay test the production of bacteriocin-like activity and resistance was found in 6 of the total of 7 isolates (5 enterococcal and 2 streptococcal). The majority of strains were sensitive to all bacteriocin producers tested. After acetone precipitation, bacteriocin precipitates were tested for thermal stability. They exhibited high stability at 37 degrees C and some of them were active even after a treatment at 95 degrees C.
Keywords: Endopeptidase K; teplota; Anti-Bacterial Agents; chemická precipitace; endopeptidasa K; antibakteriální látky; Bacteriocins; Temperature; Chemical Precipitation; Streptococcus; bakteriociny; Enterococcus